Virtual Reality Group Therapy for the Treatment of Depression: A Qualitative Study on Stakeholder Perspectives - Dilgul, Merve; Hickling, Lauren M.; Antonie, Daniela; Priebe, Stefan; Bird, Victoria J. (Frontiers in Virtual Reality, 2021)
Background: Cognitive behavioural group therapy alleviates depression by teaching patients to think and behave in more positive ways. Teletherapy (e.g., Zoom) is becoming more widely used, especially during the COVID-19 pandemic (where meeting in person is not safe). The current study explores the acceptability of taking teletherapy to the next level: Virtual Reality Group Therapy (VRGT). Methods: Semi-structured interviews were conducted to explore stakeholder views on VRGT. Ten depressed patients and ten therapists watched a demonstration video of the proposed VRGT intervention and tested the VR application using a stand-alone VR headset. In VRGT, patients will use an avatar to interact with each other and with their therapist via networked multiparticipant VR. Results: Therapists and patients generally responded favourably to the idea of doing group therapy sessions in VR. Patients especially liked the idea of remaining anonymous via an avatar. Patients and therapists both indicated that the anonymity provided by avatars could increase patient’s willingness to make disclosures (to talk more freely and honestly), which could increase participation, and could lead to better group cohesion. Conclusion: Although the findings suggested that VRGT may be more acceptable for some patients than for others, overall, the response of the patients and therapists was largely positive. Recommendations from this study could be used during the COVID-19 pandemic to deliver VRGTs. Finally, design ideas for creating a group VR world custom-designed for group therapy are discussed.